Treatment of high-grade squamous intraepithelial lesions in an area of Thailand with a high incidence of cervical cancer - Intira Sriprasert (2018)
Objective: To audit the treatment of high-grade squamous intraepithelial lesions (HSILs) at Chiang Mai University Hospital based on 12 standard requirements of the National Health Service Cervical Screening Programme. Methods: Records were reviewed of all women with histologically proven HSIL undergoing treatment at Chiang Mai University Hospital between January 2005 and May 2009. Results: Four of the standard requirements were not met: not all women underwent colposcopy before definitive treatment; the rate of specimen fragmentation was high; among women with ectocervical lesions, the rate of tissue removal to a depth of greater than 7 mm was low; and among women aged over 50 years with endocervical-margin involvement, the rate of repeat excision was low. Conclusion: This audit highlights four treatment practices that do not meet standard requirements and require detailed exploration. The development of guidelines for the treatment of cervical precancerous lesions in Thailand is challenging and merits further attention. © 2010 International Federation of Gynecology and Obstetrics All rights reserved.